FAKTOR-FAKTOR YANG MEMENGARUHI PENGAMBILAN KEPUTUSAN HEDGING - Kristanto, Harris; Rasyid, Rosmita (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
The goals is examine how influence growth opportunities, leverage, liquidity, and firm size with Hedging decisions about the production company based on Indonesia Stock Exchange during 2017-2019. Using 36 manufacturing companies as samples with purposive sampling method. The data in this study were processed using the EViews 12 program and Microsoft Excel 2010. The results of this study indicate that growth opportunities have a significant effect on hedging decision making, leverage has does not significantly affect decision making in hedging transactions, liquidity has no significant effect on hedging decision making, and firm size does not. significant affect on hedging decision making.